2017
DOI: 10.1080/16549716.2017.1368236
|View full text |Cite
|
Sign up to set email alerts
|

Mobile instant messaging for rural community health workers: a case from Malawi

Abstract: Background: Mobile instant messaging (MIM) tools, such as WhatsApp, have transformed global communication practice. In the field of global health, MIM is an increasingly used, but little understood, phenomenon. Objectives: It remains unclear how MIM can be used by rural community health workers (CHWs) and their facilitators, and what are the associated benefits and constraints. To address this gap, WhatsApp groups were implemented and researched in a rural setting in Malawi. Methods: The multi-site case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 32 publications
2
63
0
4
Order By: Relevance
“…in a group space), which can be a complex and conflictual process. For example , Pimmer, Mhango, Mzumara, and Mbvundula (2017) found that one of the prevailing challenges in the use of WhatsApp groups was the ongoing negotiation and reconciliation of users' divergent expectations regarding social versus task-oriented use of the space. What complicates this process further is that the poles which create these tensions are neither valuable nor damaging by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…in a group space), which can be a complex and conflictual process. For example , Pimmer, Mhango, Mzumara, and Mbvundula (2017) found that one of the prevailing challenges in the use of WhatsApp groups was the ongoing negotiation and reconciliation of users' divergent expectations regarding social versus task-oriented use of the space. What complicates this process further is that the poles which create these tensions are neither valuable nor damaging by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were of mixed demographics, age and gender, and training programme attendance was 100%. There were several key -All et al, 2017;Knettel et al, 2017;Pimmer, Mhango, Mzumara, & Mbvundula, 2017;Vijay & Mincy, 2015). These studies all similarly found statistically significant within-group differences be- and consideration of CHW's perspectives (Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…Studies have, however, evaluated training programmes in other areas. Several articles have evaluated various rural CHW training programme effectiveness for areas of healthcare including identification and management of disabilities, maternal health education and CVD management (Abdel‐All et al, ; Knettel et al, ; Pimmer, Mhango, Mzumara, & Mbvundula, ; Vijay & Mincy, ). These studies all similarly found statistically significant within‐group differences between pre‐ and post‐test scores demonstrating training programmes can be effective in improving knowledge of CHWs (Abdel‐All et al, ; Knettel et al, ; Vijay & Mincy, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has changed the communication landscape and made it easier and faster to share information between individuals and among groups (Pimmer & Tulenko, 2016). This is also revealed by Pimmer et al (2017) On the other hand, the use of mobile phone for Mobile Instant Messaging in nursing education and practice comes with its own challenges, some which include, but not limited to high cost, compromise to infection control efforts, interference with medical equipment (Phillippi & Wyatt, 2011), as well as ethical issues involving data security (Pimmer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This sharing of social information may serve to minimize feelings of isolation especially to those nurses operating from rural settings (Pimmer et al, 2017).…”
Section: Whatsapp Groups As a Platform For Interchange Of Social Infomentioning
confidence: 99%